Measuring Customer Satisfaction Using Marketing Mix Approach on Rice Farming Insurance Clients - Haryono, Dwi; Rosanti , Novi; Sari, Dewi Mulia; Wulandari, Riri; Sinambela , Ebenezer (Jurnal AGRISEP, 2025)
The Rice farming insurance (AUTP) program is a risk transfer mechanism designed to help farmers mitigate losses due to crop failures. This program is crucial as rice farming faces high level of risks and uncertainty. This study aims to analyze farmer’s attitudes toward AUTP and their satisfaction with the program’s attributes. Attitudes reflect farmer’s acceptance, trust, and perceptions of the benefits of the insurance, while satisfaction indicates the extent to wich their expectations are met. The research was conducted in Lampung Province, involving 161 randomly selected respondents. Farmers' attitudes were analyzed using Fishbein Multiattribute method, which evaluates their perceptions of various insurance attributes. Satisfaction levels were measured using the Customer Satisfaction Index (CSI), providing a quantitative perspective on farmer’s experiences with the AUTP Program. Base on the Fishbein Multiattribute analysis, farmer’s attitudes towards AUTP categorized as positive. This score indicates that farmers hold a favorable view of the AUTP program, with the highest scores attributed to service providers and pricing. According to CSI Analysis, farmer’s satisfaction was categorized as moderately satisfactory level.  This indicates that although farmer’s needs are largely fulfilled, some aspects of the AUTP program still require improvement. To enhance farmer’s satisfaction and partisipation, additional effors are needed, such as expanding program outreach, refining the claims process, and offering better compensation. These actions are anticipated to ensure the sustainability and effectiveness of the AUTP program in the future.